The Magdalen Girls - Alexander, V. S. (New York, NY : Kensington Books, 2017)
When her beauty provokes a lustful revelation from a young priest, sixteen-year-old Teagan is sent to one of Dublin's Magdalen Laundries for fallen women, where she befriends two other girls who help her endure the harsh captivity.
Keywords: Girls -- Institutional care -- Ireland -- Dublin -- Fiction; Reformatories for women -- Ireland -- Dublin -- Fiction; Clergy -- Sexual behavior -- Fiction; Runaway women -- Fiction; Female friendship -- Fiction; Workhouses -- Ireland -- Dublin -- Fiction; Dublin (Ireland) -- Fiction; Historical fiction; Psychological fiction